On the relation of setting and early-age strength development to porosity and hydration in cement-based materials. (April 2016) - Lootens, Didier; Bentz, Dale P.
Abstract: Previous research has demonstrated a linear relationship between compressive strength (mortar cubes and concrete cylinders) and cumulative heat release normalized per unit volume of (mixing) water for a wide variety of cement-based mixtures at ages of 1 d and beyond. This paper utilizes concurrent ultrasonic reflection and calorimetry measurements to further explore this relationship from the time of specimen casting to 3 d. The ultrasonic measurements permit a continuous evaluation of thickening, setting, and strength development during this time period for comparison with the ongoing chemical reactions, as characterized by isothermal calorimetry measurements. Initially, the ultrasonic strength-heat release relation depends strongly on water-to-cement ratio, as well as admixture additions, with no universal behavior. Still, each individual strength-heat release curve is consistent with a percolation-based view of the cement setting process. However, beyond about 8 h for the systems investigated in the present study, the various strength-heat release curves merge towards a single relationship that broadly characterizes the development of strength as a function of heat released (fractional space filled), demonstrating that mortar and/or concrete strength at early ages can be effectively monitored using either ultrasonic or calorimetry measurements on small paste or mortar specimens.